The Double Life of a Packet of Sugar. The Noise(lessness) of Communication of the Items of Everyday Use - Kołodziej, Agnieszka (Poznańskie Studia Slawistyczne, 2022)
This review discusses the book by Aleksander W. Mikołajczak and Patryk Borowiak entitled Design saszetki zcukrem. O komunikowaniu się zrzeczami (On the Design of a Packet of Sugar. How WeCommunicate with Objects). The text focuses on the interactions between people and objects, a phenomenon intrinsic to postmodernity, or the contemporary consumerist culture. The work is a peculiar biography of the packet of sugar and presents a multifaceted exploration thereof. The authors depart from the commonly conducted statistical analysis of the object of interest and instead endeavour to present the full extent of its existence and all the subsequent stages of its life, pointing to the complexity and the volatility of the process; this should be considered an innovative approach at its own right. The packet of sugar is viewed not only in the sociocultural perspective, but also through the lens of linguistics and onomastics.